A green nutraceutical study of antioxidants extraction in Cleome brachycarpa - an ethnomedicinal plant - Saleem, Tahira; Sumra, Ayesha; Khan, Samra; Zain, Maryam; Hassan, Warda; Mehdi, Sehrish; Wahid, Noor-ul-Ain; Kanwal, Samrah; Gull, Tehseen (Penerbit Universiti Kebangsaan Malaysia, 2020)
In the present study, an indigenous medical plant ‘Cleome brachycarpa’ was comparatively investigated for its antioxidant extraction for first time; using the soxhlet (traditional), microwave-assisted, and ultrasound-assisted (green) extraction methods with seven different solvents. The microwave-assisted extraction with methanol as solvent recovered the phytochemicals two-folds higher than the other methods with extraction efficiency of 370.57 ± 0.49 μg/ mg and correspondingly extracted the polyphenols: Phenolics (74.17 ± 0.61 μg GAE/mg DW), Flavonoids (65.46 ± 0.40 μg QE/mg DW), and Tannins (55.97 ± 0.85 μg CE/mg DW). The antioxidant capacity in relation with polyphenols was determined for Free radical scavenging activity and total antioxidant potential. The DPPH radical scavenging percentage of methanolic green extract of Cleome brachycarpa was found to be 81.37 ± 0.28 with IC50 of 0.30 mg/mL that matched up to the DPPH scavenging potential of Trolox. Furthermore, the ferric reducing potential was high up to 15.30 ± 0.30 μg GAE/mg DW. The correlation of antioxidant capacity with polyphenols was highly significant (p < 0.05). The green nutraceutical study has validated the ethnomedicinal importance of Cleome brachycarpa which is related to its high polyphenolic content. The findings highlight Cleome brachycarpa as a potential candidate for research and isolation of medicinal polyphenols.